2024
DOI: 10.1021/acs.est.3c08902
|View full text |Cite
|
Sign up to set email alerts
|

Micro(nano)plastics in the Human Body: Sources, Occurrences, Fates, and Health Risks

Penghui Li,
Jingfu Liu

Abstract: The increasing global attention on micro(nano)plastics (MNPs) is a result of their ubiquity in the water, air, soil, and biosphere, exposing humans to MNPs on a daily basis and threatening human health. However, crucial data on MNPs in the human body, including the sources, occurrences, behaviors, and health risks, are limited, which greatly impedes any systematic assessment of their impact on the human body. To further understand the effects of MNPs on the human body, we must identify existing knowledge gaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 186 publications
0
2
0
Order By: Relevance
“…Large pieces of PET plastics can be degraded into micro- or nanoscale fragments to form microplastics or nanoplastics following exposure to solar radiation, mechanical forces, or microorganisms . As previously reported, plastics, especially micro- and nanoplastics, are able to enter the human body. The accumulation of micro-/nanoplastics in organisms leads to adverse biological effects, thus posing a threat to organisms and human health. Previous studies have reported that the intake of PET plastics by living organisms triggers multiple biological and physiological defects, including inflammatory responses, reduced feeding activities, and energy depletion. However, the health risks and related toxicological mechanisms of PET plastics have yet to be comprehensively established, particularly the fate and metabolism of plastics in living organisms. To ascertain the fate of plastics in organisms, research on the degradation processes of plastics in vivo is required.…”
Section: Introductionmentioning
confidence: 95%
“…Large pieces of PET plastics can be degraded into micro- or nanoscale fragments to form microplastics or nanoplastics following exposure to solar radiation, mechanical forces, or microorganisms . As previously reported, plastics, especially micro- and nanoplastics, are able to enter the human body. The accumulation of micro-/nanoplastics in organisms leads to adverse biological effects, thus posing a threat to organisms and human health. Previous studies have reported that the intake of PET plastics by living organisms triggers multiple biological and physiological defects, including inflammatory responses, reduced feeding activities, and energy depletion. However, the health risks and related toxicological mechanisms of PET plastics have yet to be comprehensively established, particularly the fate and metabolism of plastics in living organisms. To ascertain the fate of plastics in organisms, research on the degradation processes of plastics in vivo is required.…”
Section: Introductionmentioning
confidence: 95%
“… 2 , 3 , 4 There are evidences of MNPs in blood, placental, and other human tissues, posing a risk to human health. 5 However, the pathways through which humans are exposed to MNPs remain poorly understood. One potential direct exposure route is through the release of MNPs from intravenous infusion products (IVIPs) into the bloodstream.…”
Section: Before You Beginmentioning
confidence: 99%